PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DAN GAYA BELAJAR TERHADAP KEMAMPUAN MENYIMAK BAHASA INGGRIS (Studi Pada Siswa SMK Swasta Jakarta Pusat) - Deswin, Yendri (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2018)
This research aims to know how impact of using learning media and student learning style for the student English listening skill. This research was conducted by distributing questionnaires and term test directly ofÂ  the Private Vocational School of Central Jakarta as using 50 students that choosing as simple random sampling technique. Data were analyzed by using descriptive statistic method, Parson oefficient, and regression analyze. Result of this research shows that using learning media and learning style for student significantly impact of capabilities of English listening skill student at vocational school in Central Jakarta